The Relationship between Core Stability Muscles Isometric Strength and Endurance with the Postural Control and Walking Endurance in Patients with Multiple Sclerosis - Behnam Moradi; Seyed Sadreddin Shojaedin (Islamic Azad University, Hamedan Branch, 2018)
Objective: multiple sclerosis is one of the most common diseases which affect adults’ central neural system. The aim of this study was to assess the relationship between core stability muscles isometric strength and endurance with the postural control and walking endurance in patients with multiple sclerosis (MS). Methods: To this end, 35 male patients (incapability scale 1to 4, aged between 25 to 35, with the ability to walk independently) from Tehran MS association participated in this study voluntarily. In order to evaluate the core muscles isometric strength and endurance, and the postural control  of the patients with multiple sclerosis, two sets of tests (using barometer and keeping the time) and berg balance tests and 6-minute walk were utilized. In order to examine the relationship between and among the tests, Pearson correlation coefficient (with the significance level of 0.95 and p value≤0.05) was used. Results: The relationship between core muscles isometric strength and endurance among the MS patients (Leg Abductors Strength r= 0.629, leg External Rotators Strength r= 0.492, Trunk Flexor Endurance r = 0.546, Trunk Extensors Endurance r = 0.552, Trunk lateral Flexor Endurance r = 0.564) and their balance was significant (direct and positive relationship). On the other hand, no significant relationship was found between core muscles isometric tests with 6-minute with walk functional among the patients multiple sclerosis. Conclusion: Despite the significant relationship between core muscles isometric strength and endurance in patients MS on one of the functional capability variables (balance), it should be stated that taking advantage of other methods (dynamic methods and methods like Electromyography) is required in order to achieve more verified and certain results.